Severe childhood burns in the Czech Republic: risk factors and prevention - Alexander Martin Čelko; Michal Grivna; Jana Dáňová; Peter Barss (The World Health Organization, 2009)
OBJECTIVE: To assess risk factors for paediatric burn injuries in the Czech Republic and to suggest preventive measures. METHODS: This study included all children aged 0-16 years hospitalized during 1993-2000 at the Prague Burn Centre and data from the Czech Ministry of Health on national paediatric burn hospitalizations during 1996-2006. Personal, equipment and environmental risk factors were identified from hospital records. FINDINGS: The incidence of burn admissions among 0-14 year-olds increased from 85 to 96 per 100 000 between 1996 and 2006, mainly due to a 13% increase among 1-4 year-olds. Between 1993-2000 and 2006, the proportion of burn victims in the country hospitalized at the Prague Burn Centre increased from 9% to 21%. Detailed data were available on 1064 children (64% boys). Around 31% of all burn hospitalizations were in 1 year-olds. Some 79% of burns occurred at home: 70% in the kitchen, 14% in the living room or bedroom and 11% in the bathroom. Of the 18% occurring outdoors, 80% involved boys. Scalds from hot liquids accounted for 70% of all burns. The mean hospital stay was 22 days for boys and 18 days for girls. CONCLUSION: Most burns involved scalds from hot liquids at home: beverages in kitchens and water in bathrooms. There is a need for passive preventive measures, such as redesigned domestic cooking and eating areas, safer electrical kettles and temperature control devices for bathrooms. Educational programmes should be developed for parents and caregivers. A national plan for child burn prevention with specific targets would be helpful.